2011
DOI: 10.1068/p6856
|View full text |Cite
|
Sign up to set email alerts
|

Different Signals of Personality and Health from the Two Sides of the Face

Abstract: Abstract. Previous studies demonstrate that people with different personality traits have different looking faces. We investigated whether personality and health information are differently signalled by the two hemifaces. Using composite images created from women with high and low scores on health and personality dimensions, we investigated discrimination accuracy with original and mirrored hemifaces. By comparing discrimination accuracy for particular types of hemiface, we address issues regarding both the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Similar accuracy levels of trait discrimination are reported by Kramer and Ward (2011) using hemi-face versions of these stimuli (that is, presenting just the left or right half of the stimuli). Therefore, we focused our analyses upon the most robustly discriminated traits of Neuroticism, Extraversion, and Agreeableness.…”
Section: Methodssupporting
confidence: 80%
“…Similar accuracy levels of trait discrimination are reported by Kramer and Ward (2011) using hemi-face versions of these stimuli (that is, presenting just the left or right half of the stimuli). Therefore, we focused our analyses upon the most robustly discriminated traits of Neuroticism, Extraversion, and Agreeableness.…”
Section: Methodssupporting
confidence: 80%
“…This finding is in accordance with the finding that the right side of the owner's face ( right hemiface ) affects the perception of attractiveness, age and gender (Zaidel et al, 1995; Burt and Perrett, 1997; Dunstan and Lindell, 2012) more than the left side ( left hemiface ) but is in some contrast to findings that emotional aspects can be derived better and more accurately from the left side of the owner's face (e.g., Zaidel et al, 1995; Kramer and Ward, 2011; Lindell, 2013a,b; Low and Lindell, 2016). However, with respect to the perceived attractiveness , we found comparative lager effects for the left hemiface , contrasting past research by others (for instance, Zaidel et al, 1995; Burt and Perrett, 1997; Dunstan and Lindell, 2012; but also see Sitton et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…However, with respect to the perceived attractiveness , we found comparative lager effects for the left hemiface , contrasting past research by others (for instance, Zaidel et al, 1995; Burt and Perrett, 1997; Dunstan and Lindell, 2012; but also see Sitton et al, 2006). It is important to mention that past research (but see Kramer and Ward, 2011) did not use 2D stimuli generated from real 3D face models for that kind of research question. Schneider et al (2012) suggested that differences in perceptual aspects (e.g., perceived body weight on the basis of faces) are strongly dependent on depth information, hence viewing perspective affects respective ratings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This describes human personality in terms of five dimensions; extraversion, agreeableness, openness (sometimes called intellect: Goldberg, 1990 ), neuroticism (sometimes contrasted to emotional stability), and conscientiousness (McCrae and Costa, 1987 ; Goldberg, 1990 ). The Big Five model applies to both self and peer ratings (see Goldberg, 1993 ; John and Srivastava, 1999 for reviews), and a number of studies now have looked at judgments of strangers on the Big Five personality dimensions from face photographs, or photographs with minimal target information; mostly entirely to examine the accuracy of these judgments (Watson, 1989 ; Penton-Voak et al, 2006 ; Little and Perrett, 2007 ; Beer and Watson, 2008 ; Naumann et al, 2009 ; Back et al, 2010 ; Kramer and Ward, 2010 , 2011 ; Ivcevic and Ambady, 2012 ; Jones et al, 2012 ; Leikas et al, 2013 ). This raises the question of how these Big Five personality characteristics relate to the broad factors of facial first impressions, since these two literatures have not been integrated.…”
Section: Introductionmentioning
confidence: 99%